REALIZATION OF LINGUISTIC AND FORMULAIC COMPETENCES IN CLASSROOM INTERACTION - Sekar Meifi Andari; Widhiyanto (Universitas Negeri Manado, 2021)
This study aimed to investigate the types and the most dominant type of formulaic competence, how teacher and students differ in using the expressions, and how is the relationship between linguistic and formulaic competence in classroom interactions. The subjects of this study were one English teacher and 36 students of tenth grade in the academic year of 2020/2021. This study used a qualitative method. The data were collected through observation and documentation. In order to analyse the data, the theory proposed by Biber et al. (1999) and Celce-Murcia (2007) were used. The study revealed that there were five types of formulaic competence used in classroom interactions as Biber et al. (1999) proposed. They were collocations, idiomatic phrases, lexical bundles, binominal expressions, and inserts. The most dominant type used was inserts with 70% and followed by lexical bundles with 19%, collocations (5%), idiomatic phrases with 3%, and binominal expressions with 3%. In the differences between the teacher and students used of the expressions, the teacher used all five types of formulaic competence, while the students only used four types of formulaic competence and disregarding the use of idiomatic phrases. During the interactions, the teacher used more varies expressions than the students. Then, the findings also showed that there was a relationship between linguistic and formulaic competence.